2019
DOI: 10.30534/ijatcse/2019/26862019
|View full text |Cite
|
Sign up to set email alerts
|

The Method of Hidden Transmitters Detection based on the Differential Transformation Model

Abstract: The article investigates the method of calculating the basic parameters of random signals emitted by hidden transmitters. The method is based on a mathematical model of differential signal transformations within the framework of correlation theory. It is proved that under certain initial conditions the expected value of a random signal consists of the sum of all expectations of the differential spectrum. A method for numeric calculating of the variance, which consists of determining the differential spectrum a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 5 publications
0
5
0
1
Order By: Relevance
“…Various acquisition methods and algorithms for processing original images help accurately determine the qualitative and quantitative characteristics of the state of different territories of our planet. Works [5,6] described the method of obtaining data based on correlation theory, which makes it possible to effectively recognize and classify them. It is shown that the construction of a suitable classifier could significantly improve the efficiency of further image processing operations: localization, recognition, search, and tracking of covered by fires and forecasting the future occurrence of this natural disaster with further consequences was not considered.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
See 1 more Smart Citation
“…Various acquisition methods and algorithms for processing original images help accurately determine the qualitative and quantitative characteristics of the state of different territories of our planet. Works [5,6] described the method of obtaining data based on correlation theory, which makes it possible to effectively recognize and classify them. It is shown that the construction of a suitable classifier could significantly improve the efficiency of further image processing operations: localization, recognition, search, and tracking of covered by fires and forecasting the future occurrence of this natural disaster with further consequences was not considered.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…Thus, our review of literary sources [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] revealed that they lack analysis based on a mathematical apparatus that detects the influence of harmful factors, and it is not specified where and how the information obtained and processed is stored. The issues of efficiency in determining forest areas that were affected by forest fires, with their further classification, assessment of burned areas, and analysis of relationships between parameters that negatively affect the tree stand remain unsolved.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…This algorithm is an exact copy of the block encryption algorithm, with one exception. The new one defines and establishes a permutation table for nonlinear transformation, which is absent in the old algorithm, and the task of its elements was entirely in the hands of the people implementing the algorithm [18][19][20][21]. Theoretically, if you self-identify the elements of the permutation table and keep the table secret, it will increase the longevity of the encryption algorithm (this actually increases the length of the key)…”
Section: Literature Analysis and Problem Statementmentioning
confidence: 99%
“…Radiation analysis to search for suspicious objects is more complicated and less popular, so, it needs more in-depth consideration. An example of such a model is given in the publication of O. Laptev et al [3]. In addition, Savchenko's publications [4] and [5] consider the possibility of weak signals passing through shielding surfaces.…”
Section: Related Work Overviewmentioning
confidence: 99%